Sociological Perspectives to Impact of Strike Actions in Nigerian Tertiary Institutions on the Social Adjustment of University of Lagos Undergraduates. - Emeri, Patience Nnenne; Adeyemo, Caleb Oluwabukolami (NIU Journal of Social Sciences, 2025)
Strike action is a legitimate means through which workers make their employers accede to their demands. Nigerian tertiary institution workers have employed the means over the years in their labour-relations with their government employers. Although the use of strike actions has not always yielded the desired results, it would sadly remain a legitimate option when every other means of engagement fails. The impact this may have on the products of the system and the society is a concern to all education stakeholders. This research hence, investigated the impact of strike actions on social adjustments among undergraduate students of the University of Lagos. The study adopted a descriptive survey research design, with a sample size of 280 undergraduate students drawn from study population using proportionate random sampling technique. Five hypotheses guided the study. A researcher-developed questionnaire titled Impact of Strike Actions on Social Adjustment Questionnaire (ISASAQ) with r = 0.71 was used for data collection, Chi-square and ANOVA statistical tools were employed for data analysis at 0.05 level of significance. The findings of the study revealed that incessant strike has a significant impact on the schools’ academic programme, students’ interest in education and students’ interpersonal relationships. Also, there is a significant age impact of incessant strike on social adjustment among undergraduate students at the University of Lagos. Based on the research findings, the study recommends; fostering positive labour relations and open communication to minimize the frequency and duration of strikes and adopting in addition, flexible academic programmes that allow for alternative modes of learning during strike periods to alleviate disruptions to students' education. Also, strengthening student support services, promoting transparency and timely communication, and prioritizing initiatives that foster social integration is essential to support students' social adjustment during periods of strikes. Keywords: Incessant strikes, Education, Interpersonal relationship, Social Adjustment.